Multi-response optimisation in a three-link leaf-spring model - (:unkn) unknown (INDERSCIENCE ENTERPRISES LTD, 2005)
The simulation of road loads in truck suspensions generally requires leaf-spring models. There are many models in the literature. In this study the three-link leaf-spring model was compared with the test results. An attempt was made to establish the model by predicting accurate results. In order to perform this task, standard tests were performed to obtain the relationship between the torque and angular displacement. After that the corresponding three-link model was generated, and run using the ADAMS solver. After obtaining the desired model the parameters effecting the acceleration for the driver seat were optimised by means of an ANOVA method. The parameters are the length of the leaf spring, the material properties of the leaf spring and the stiffness of the springs connected to the front panel. The reduced acceleration for the driver seat was determined by the response surface regression method.
Keywords: leaf spring; optimisation; three-link